Development of Stress Management Guidebook to Prevent Academic Burnout on Vocational High School Students - Tahta, Gihza Hasnutya; Setiyowati, Arbin Janu; Utami, Nugraheni Warih; Ummah, Umi Safiul (citeus, 2025)
Students must be aware of academic burnout, as it can reduce their learning achievement. This study aims to develop a stress management guidebook to prevent academic burnout in vocational high school students. This guidebook can be used by counselors as a reference in providing guidance services to vocational students who have problems related to academic burnout. This manual is equipped with an academic burnout scale to measure the level of student academic burnout. The development model in this study used the Borg and Gall development research design. In this study, we used five stages, consisting of pre-survey, product design, design validation, product testing, and final product preparation. The research instruments were material expert assessment instruments, media expert assessment instruments, and assessment instruments for prospective product users. The obtained data were analyzed using descriptive percentages and inter-rater agreement. The results of the study indicated that the stress management guide meets the acceptability criteria, so it is appropriate to be used as a medium for counselors to facilitate the development of students’ stress management to prevent academic burnout.